The Dementia Engagement Modelling Program (DEMP): a novel Australian model of care for aged care residents affected by COVID-19 - Atee, Mustafa; Morris, T.; Alford, M. (2022)
Like other countries, aged care homes in Australia have been significantly affected by the COVID-19 pandemic. To ensure the safety of residents and staff, lockdown, and social restrictions (e.g., limited or no visits from family) have been introduced across Australia. These measures caused tremendous emotional, psychological, and physical burdens on residents, particularly those living with dementia. In response to the pandemic, the Australian Government has funded the Aged Care COVID-19 Grief and Trauma support package for older people receiving aged care, their families, and aged care staff. Part of this package is the Dementia Engagement Modelling Program (DEMP), a free national support program developed by Dementia Support Australia, HammondCare to help staff support residents whose wellbeing have been affected by COVID-19 with tailored engagement strategies. The program represents a first line multimodal support for people living with dementia in residential aged care who may have experienced withdrawal, frustration, or fear and at a greater risk of developing behaviors and psychological symptoms of dementia (BPSD), such as apathy, anxiety, and depression. Through a multidisciplinary team of dedicated consultants, the program delivers best practice, person-centered engagement strategies to support staff, providing meaningful engagement, comfort, and reassurance to residents living with dementia. DEMP consultants work collaboratively and closely with lifestyle and care staff to develop tailored activities and provide appropriate resources (e.g., brokerage items such as music therapy) for engagement. DEMP will also provide support and coaching to staff for the individual or small groups to ensure that both staff and residents gain the full benefit from the program. The eligibility criteria for DEMP support include aged care homes that: 1) experienced an outbreak of COVID-19 or those subject to a precautionary lockdown, and/or 2) sought engagement plans and strategies for residents living with dementia, or those at risk of developing BPSD due to COVID-19 restrictions. This descriptive study will discuss the DEMP's model of care, eligibility criteria, activities, and outcomes and provide case examples that can guide meaningful engagement for other aged care residents living in other countries during COVID-19.